Measurement of Bone Mineral Content to Facilitate an Objective Evalution of Limp Function in the Dog - Svalastoga, E.; Petersen, M. M.; Wenck, A.; Strøm, Henriette (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
The aim of this study was to evaluate the feasibility of using measurements of bone mineral content (BMC) and bone mineral density (BMD) by dual photon absorptiometry (DPA; Gadolinium-153), as an objective measure of limb functional status in the dog. The in vitro accuracy error expressed as the standard error of the estimate (SEE) for BMC and BMD measurements was 3.2% and 1.1% respectively, and the precision in vivo for measurements of BMC and BMD in the distal diaphysis of the tibia and fibula was 2.1% and 1.9% respectively. A significant difference in bone mineral between right and left leg was not found in normal dogs, and in these dogs the average percentage intra-individual difference, between bone mineral in the legs with the highest bone density and the legs with the lowest density, was 2.2% and 3.7% for BMC and BMD respectively. However the BMC and BMD in eight clinical cases of unilateral lameness were significantly decreased in the affected legs, when compared to the healthy contralateral legs, by 20.4% (P = 0.01) and 18.3% (P = 0.01)respectively. Measurements of BMC and BMD by DP A in weight-bearing extremities in the dog showed that bone mineral is highly sensitive to decreased loading of the extremity. This method might well be used not only as an objective measure of limb activity, but also for measurement of prospective changes in bone mineral, following treatment of musculoskeletal diseases and injuries.The feasibility of using bone mineral measurements by dual photon absorptiometry, as an objective measure of limb functional status in the dog, was evaluated. Precision and accuracy were calculated from in vitro and in vivo studies. In eight cases of unilateral lameness bone mineral was significantly decreased (20%) in the affected legs when compared to the healthy contralateral legs.
Keywords: Bone dendity; dual photon absorptiometry; dogs lameness